Cell‐based therapy to reduce mortality from COVID‐19: Systematic review and meta‐analysis of human studies on acute respiratory distress syndrome. (29th May 2020) - Qu, Wenchun; Wang, Zhen; Hare, Joshua M.; Bu, Guojun; Mallea, Jorge M.; Pascual, Jorge M.; Caplan, Arnold I.; Kurtzberg, Joanne; Zubair, Abba C.; Kubrova, Eva; Engelberg‐Cook, Erica; Nayfeh, Tarek; et al.
Abstract: Severe cases of COVID‐19 infection, often leading to death, have been associated with variants of acute respiratory distress syndrome (ARDS). Cell therapy with mesenchymal stromal cells (MSCs) is a potential treatment for COVID‐19 ARDS based on preclinical and clinical studies supporting the concept that MSCs modulate the inflammatory and remodeling processes and restore alveolo‐capillary barriers. The authors performed a systematic literature review and random‐effects meta‐analysis to determine the potential value of MSC therapy for treating COVID‐19‐infected patients with ARDS. Publications in all languages from 1990 to March 31, 2020 were reviewed, yielding 2691 studies, of which nine were included. MSCs were intravenously or intratracheally administered in 117 participants, who were followed for 14 days to 5 years. All MSCs were allogeneic from bone marrow, umbilical cord, menstrual blood, adipose tissue, or unreported sources. Combined mortality showed a favorable trend but did not reach statistical significance. No related serious adverse events were reported and mild adverse events resolved spontaneously. A trend was found of improved radiographic findings, pulmonary function (lung compliance, tidal volumes, PaO2 /FiO2 ratio, alveolo‐capillary injury), and inflammatory biomarker levels. No comparisons were made between MSCs of different sources. Abstract : In ARDS, pro‐inflammatory cytokines contribute to the disruption of the alveolar – capillary membrane, edema, and pneumocyte damage. MSCs modulate the inflammatory milieu by T‐cell and macrophage redirection, and anti‐inflammatory cytokine production. Clinical trials assessing MSC therapy in ARDS have shown that MSCs have been associated with a favorable trend in morality reduction, pulmonary function improvement, and cytokine correction.